Relationship between Substance Abuse and Multidrug-Resistant Tuberculosis - Afroz, Sayda; Flora, Meerjady Sabrina (Ibrahim Medical College Journal, 2013)
This case control study was conducted between January to June 2010 to determine the relationship between substance abuse and multidrug- resistant tuberculosis. A total of 73 cases were selected purposively, from culture- positive multidrug- resistant tuberculosis patients admitted in the National Institute of Diseases of the Chest and Hospital, Dhaka and compared with 81 un-matched controls, recruited from the cured patients of pulmonary tuberculosis who attended several DOTS centers of Nagar Shastho Kendra under Urban Primary Health Care Project in Dhaka city. Data were collected by face to face interview and documents review, using a pre- tested structured questionnaire and a checklist. Multidrug- resistance was found to be associated with smoking status (÷2 = 11.76; p = 0.01) and panmasala use (÷2 = 8.28; p = 0.004). The study also revealed that alcohol consumption and other substance abuse such as jarda, sadapata, gul, snuff, heroine, cannabis, injectable drugs was not associated with the development of multidrug- resistant tuberculosis. Relationship between substance abuse and multidrug- resistant tuberculosis are more or less similar in the developing countries. Bangladesh is not out of this trend. The present study revealed the same fact, which warrants actions targeting specific factors. Further study is recommended to assess the magnitude and these factors related to the development of multidrug- resistant tuberculosis in different settings in our country. DOI: http://dx.doi.org/10.3329/imcj.v6i2.14729 Ibrahim Med. Coll. J. 2012; 6(2): 50-54